Effects of ball milling on the physicochemical and sorptive properties of biochar: Experimental observations and governing mechanisms - Lyu, Honghong; Gao, Bin; He, Feng; Zimmerman, Andrew R.; Ding, Cheng; Huang, Hua; Tang, Jingchun (Environmental pollution (1987), 2018)
With the goal of combining the advantages of ball-milling and biochar technologies, a variety of ball-milled biochars (BM-biochars) were synthesized, characterized, and tested for nickel (Ni(II)) removal from aqueous solution. Ball milling increased only the external surface area of low temperature biochars, but still dramatically enhanced their ability to sorb aqueous Ni(II). For higher temperature biochars with relatively low surface area, ball milling increased both external and internal surface area. Measurements of pH, zeta potential, stability, and Boehm titration demonstrated that ball milling also added oxygen-containing functional groups (e.g., carboxyl, lactonic, and hydroxyl) to biochar's surface. With these changed, all the BM-biochars showed much better Ni(II) removal efficiency than unmilled biochars. Ball-milled 600 °C bagasse biochar (BMBG600) showed the greatest Ni(II) adsorption capacity (230–650 compared to 26–110 mmol/kg for unmilled biochar) and the adsorption was dosage and pH dependent. Compared with the unmilled biochar, BMBG600 also displayed faster adsorption kinetics, likely due to an increase in rates of intra-particle diffusion in the latter. Experimental and modeling results suggest that the increase in BM-biochar's external and internal surface areas exposed its graphitic structure, thus enhancing Ni(II) adsorption via strong cation-π interaction. In addition, the increase in acidic surface functional groups enhanced Ni(II) adsorption by BM-biochar via electrostatic interaction and surface complexation. Ball milling thus has great potential to increase the efficiency of environmentally friendly biochar for various environmental applications. [Display omitted] •BM-biochars were synthesized combining the advantages of ball-milling and biochar technologies.•Ball milling dramatically increased the external and internal surface area of biochars.•Ball milling increased the amount of acidic surface functional groups.•Ball milling increased sorption ability of biochars to Ni(II) with fast kinetics and large capacity. Ball milling increased the external and internal surface area of biochars, and thus increased sorption ability of biochars to Ni(II) with fast kinetics and large capacity.